Traditional Foods From Maize (Zea mays L.) in Europe - Revilla, Pedro; Alves, Mara Lisa; Andelković, Violeta; Balconi, Carlotta; Dinis, Isabel; Mendes-Moreira, Pedro; Redaelli, Rita; Ruiz de Galarreta, Jose Ignacio; Vaz Patto, Maria Carlota; Žilić, Sladana; Malvar, Rosa Ana (Frontiers in Nutrition, 2022)
Maize (Zea mays L.) is one of the major crops of the World for feed, food, and industrial uses. It was originated in Central America and introduced into Europe and other continents after Columbus trips at the end of the fifteenth Century. Due to the large adaptability of maize, farmers have originated a large variability of genetic resources with wide diversity of adaptation, characteristics, and uses. Nowadays, in Europe, maize is mainly used for feed, but several food specialties were originated during these five centuries of maize history and became traditional food specialties. This review summarizes the state of the art of traditional foodstuffs made with maize in Southern, South Western and South-Eastern Europe, from an historic evolution to the last research activities that focus on improving sustainability, quality and safety of food production.